Pelatihan Inovasi Aromaterapi Berbasis Cokelat sebagai Hilirisasi Industri Kakao Non-Makanan di Luwu Utara - Hurria; Anggra Alfian; Altri Wahida; Besse Eka Putri Deswinda; Karina Nurul Fajri (Politeknik Piksi Ganesha Indonesia, 2024)
North Luwu Regency in Indonesia is known for its cocoa production, which was once the largest in the area. The Regional Medium-Term Development Plan (RPJMD) of North Luwu Regency has identified cocoa as a superior regional commodity. The Chalodo Sibali Resoe cocoa processing industry, part of the Makkuraga Sibali Resoe Industrial Producer Cooperative, leads the cocoa bean processing industry in North Luwu. This community partnership program aims to develop new non-food products and boost sales of Chalodo products to increase business profits. The program includes socialization, training, technology application, mentoring and evaluation, and ensuring program sustainability. As part of the community service activities, efforts to develop chocolate-based aromatherapy innovations have been successful, resulting in improved partner skills and the creation of two commercial products.